Leveraging the Power of the Indian Diaspora: US–India Higher Education Relations - Bhandari, Rajika (International Higher Education, 2025)
<h3 id="the-growing-indian-diaspora-in-the-united-states-serves-as-a-critical-link-for-furthering-usindia-higher-education-relations-yet-its-role-and-potential-are-often-overlooked-this-article-highlights-the-ways-in-which-the-diaspora-on-us-campusesfrom-faculty-to-presidents-and-chancellors-to-second-generation-indian-american-studentsis-furthering-this-critical-relationship-the-role-of-institutional-partnerships-and-national-policies-is-also-discussed" data-pm-slice="1 1 []">The growing Indian diaspora in the United States serves as a critical link for furthering US–India higher education relations, yet its role and potential are often overlooked. This article highlights the ways in which the diaspora on US campuses—from faculty to presidents and chancellors, to second-generation Indian American students—is furthering this critical relationship. The role of institutional partnerships and national policies is also discussed.